Multi-center real-world comparison of the fully automated Idylla™ microsatellite instability assay with routine molecular methods and immunohistochemistry on formalin-fixed paraffin-embedded tissue of colorectal cancer - Velasco, Ana; Tokat, Fatma; Bonde, Jesper; Trim, Nicola; Bauer, Elisabeth; Meeney, Adam; de Leng, Wendy; Chong, George; Dalstein, Véronique; Kis, Lorand L; Lorentzen, Jon A; Tomić, Snjezana; et al. (Virchows Archiv, 2021)
Microsatellite instability (MSI) is present in 15-20% of primary colorectal cancers. MSI status is assessed to detect Lynch syndrome, guide adjuvant chemotherapy, determine prognosis, and use as a companion test for checkpoint blockade inhibitors. Traditionally, MSI status is determined by immunohistochemistry or molecular methods. The Idylla™ MSI Assay is a fully automated molecular method (including automated result interpretation), using seven novel MSI biomarkers (ACVR2A, BTBD7, DIDO1, MRE11, RYR3, SEC31A, SULF2) and not requiring matched normal tissue. In this real-world global study, 44 clinical centers performed Idylla™ testing on a total of 1301 archived colorectal cancer formalin-fixed, paraffin-embedded (FFPE) tissue sections and compared Idylla™ results against available results from routine diagnostic testing in those sites. MSI mutations detected with the Idylla™ MSI Assay were equally distributed over the seven biomarkers, and 84.48% of the MSI-high samples had ≥ 5 mutated biomarkers, while 98.25% of the microsatellite-stable samples had zero mutated biomarkers. The concordance level between the Idylla™ MSI Assay and immunohistochemistry was 96.39% (988/1025); 17/37 discordant samples were found to be concordant when a third method was used. Compared with routine molecular methods, the concordance level was 98.01% (789/805); third-method analysis found concordance for 8/16 discordant samples. The failure rate of the Idylla™ MSI Assay (0.23%; 3/1301) was lower than that of referenced immunohistochemistry (4.37%; 47/1075) or molecular assays (0.86%; 7/812). In conclusion, lower failure rates and high concordance levels were found between the Idylla™ MSI Assay and routine tests.
Keywords: laboratorní automatizace; Tissue Fixation; formaldehyd; Humans; mikrosatelitní nestabilita; mutační analýza DNA; zalévání tkání do parafínu; Biomarkers, Tumor; Microsatellite Instability; Predictive Value of Tests; mutace; Multi-center study; lidé; Idylla™ MSI assay; Immunohistochemistry; imunohistochemie; reprodukovatelnost výsledků; nádorové biomarkery; DNA Mutational Analysis; FFPE clinical tissue samples; Automation, Laboratory; kolorektální nádory; Reproducibility of Results; Colorectal cancer; prediktivní hodnota testů; fixativa; fixace tkání; Paraffin Embedding; Microsatellite instability; Fixatives; Mutation; Colorectal Neoplasms; Formaldehyde